Indonesia Black Cumin (Nigella sativa L.) Seeds Extract as Ameliorant Reproductive Function in Type-2 Diabetes Mellitus - Retno Susilowati; Nailirrohmah Hidayatin; Amalia Rizka Diana; Tri Kustono Adi (Biogenesis: Jurnal Ilmiah Biologi, 2020)
Diabetes initiates augmented damage in levels of nuclear and mitochondrial DNA in males. As a result, the sperm DNA is affected, as well, leading to lower levels of fecundity and influencing reproductive health. This study aims to improve male reproductive function and oxidative stress status in diabetic rats. Combination High Fat Diet (HFD) and Streptozotocin (STZ) injection 30 mg/kg intraperitoneally are the initiations of DM-2 for 14 weeks. Treat therapy using 80% ethanol extract of black cumin seeds takes five weeks. Based on parametric test on ANOVA test results followed by Duncan Multiple Range Tests on the concentration, abnormalities of spermatozoa and Super Oxide Dismutase (SOD) effects and the Kruskal-Wallis test followed by the Mann-Whitney test on non-parametric data of the spermatozoa motility and Malondialdehyde (MDA) levels, showed that obtaining black cumin dose 48 is an effective dose in improving sperm quality and stress oxidation level. It has the same effect with metformin, even has MDA level less than normal rats. This study finds out Ns-48 is an effective dose of ethanol extract of black cumin seeds to improving spermatozoa quality and stress oxidation level, so that it becomes valuable information for research related to the improvement of reproductive function in diabetes mellitus disease.